Carbide precipitation characteristics in additive manufacturing of Co-Cr-Mo alloy via selective electron beam melting. (15th January 2018) - Tan, X.P.; Wang, P.; Kok, Y.; Toh, W.Q.; Sun, Z.; Nai, S.M.L.; Descoins, M.; Mangelinck, D.; Liu, E.; Tor, S.B.
Abstract: Carbide precipitation plays a key role in determining mechanical properties of Co-Cr-Mo alloy. Precipitation characteristics of carbides in selective electron beam melting (SEBM)-fabricated Co-Cr-Mo parts have been investigated by atom probe tomography and transmission electron microscopy. We observe co-existence of two types of carbides, i.e. M23 C6 and M6 C, which are formed into continuous carbide thin films along columnar grain boundaries. The carbide thin film is found to precipitate coherently with one γCo grain while incoherently with another adjacent one. Moreover, columnar carbide chains or clusters consisting of nanometer-sized, cuboidal particles are precipitated coherently with surrounding γCo phase within interdendritic regions. Graphical abstract: Image 1